Implementation Of The Use Of Powerpoint Media In Islamic Religious Education Learning At Private Junior High School Of Galih Agung Deli Serdang Regency - Ahdar Muslim; Adjeng Dwi Cahyanie; Saiful Bahri (International journal of technology and education research, 2026)
The low attention student to method lecture conventional in Islamic Religious Education learning in the digital era demands existence transformation of teaching media to be more visual and interactive. However reality on the ground show that utilization of PowerPoint media in schools private Still often limited to digitalization text without enrichment essential multimedia elements. Research This aim For describe in a way deep implementation use of PowerPoint media in Islamic Religious Education learning at Galih Agung Private Middle School, Deli Serdang. Using approach qualitative with method studies field, data collected through observation participatory passive, interview deep with Islamic Religious Education teachers and students class VIII, and review documentation teaching tools, then analyzed using the interactive model of Miles and Huberman. The results of the study disclose that PowerPoint implementation in progress in a way structured in three stages, namely conditioning opening spiritual atmosphere through appearance calligraphy and murottal, delivery core material that utilizes animation worship movements and exemplary videos For visualize draft abstract, and evaluation learning based quiz interactive that transforms evaluation become experience fun. However Thus, the effectiveness implementation This hampered by three constraint main nature systemic, namely limitations the number of LCD projectors is only two units for nine group study, supply electricity that is not stable and frequent outage suddenly, and investment time significant that must be devoted to teachers designing quality slides in the middle dense burden administrative. Implementation results study push addition means projector and power supply Power reserves, reduction burden teacher administration, formation community Study professional For share source Islamic visual power, as well as training design sustainable and contextual digital instruction.